Increased miR-142-3p Expression Might Explain Reduced Regulatory T Cell Function in Granulomatosis With Polyangiitis - Dekkema, Gerjan J.; Bijma, Theo; Jellema, Pytrick G.; Van Den Berg, Anke; Kroesen, Bart-Jan; Stegeman, Coen A.; Heeringa, Peter; Abdulahad, Wayel H.; Sanders, Jan-Stephan (Frontiers in Immunology, 2019)
Objectives: Regulatory T cells (Tregs) are frequently functionally impaired in patients with granulomatosis with polyangiitis (GPA). However, the mechanism underlying their impaired function is unknown. Here, we hypothesized that Treg dysfunction in GPA is due to altered microRNA (miRNA) expression. Methods: RNA isolated from FACS-sorted memory (M) Tregs (CD4+CD45RO+CD25+CD127-) of 8 healthy controls (HCs) and 8 GPA patients without treatment was subjected to miRNA microarray analysis. Five differentially expressed miRNAs were validated in a larger cohort by reverse transcriptase quantitative polymerase chain reaction (RT-qPCR). An miRNA target gene database search revealed targets that were tested with RT-qPCR in MTregs from patients and HCs. cAMP levels were measured using flow cytometry. Results: Microarray analysis revealed 19 differentially expressed miRNAs, of which miR-142-3p was confirmed to be significantly upregulated in MTregs from GPA patients compared to those from HCs (1.9-fold, p=0.03). In vitro overexpression of miR-142-3p lowered the suppressive capacity of MTregs (2.1-fold, p=0.03), and miR-142-3p expression correlated negatively with the suppressive capacity (rho=-0.446, p=0.04). Overexpression of miR-142-3p significantly decreased cAMP levels (p=0.02) and tended to decrease the mRNA levels of a predicted target gene, adenylate cyclase 9 (ADCY9) (p=0.06). In comparison to those from HCs, MTregs from GPA patients had lower ADCY9 mRNA levels (2-fold, p=0.008) and produced significantly less cAMP after stimulation. Importantly, induction of cAMP production in miR-142-3p overexpressed MTregs by forskolin restored their suppressive function in vitro. Conclusion: Overexpression of miR-142-3p in MTregs from GPA patients might cause functional impairment by targeting ADCY9, which leads to the suppression of cAMP production.